Nivel de desempeño de la fuerza de ventas del Almacén Créditos Económicos - Valladares Baños, Cesar John (2020)
The performance of the workers is a very important element in the performance of the daily activities of any company, with the research that was carried out it was possible to determine the factors that cause problems in the performance level of the warehouse sales force. the city of Babahoyo. A qualitative research methodology was used and surveys were applied to employees, with this information it was possible to find factors such as motivation, remuneration, sales goals, training, job security, among others, with which we proceeded to make the conclusions of the case study.